The Revealed Value of Time in Air Travel - Vany, Arthur De (The Review of Economics and Statistics, 1974)
THIS PAPER DEMONSTRATES A NEW REVEALED PREFERENCE APPROACH TO VALUATING TIME. THE FULL-PRICE DEMAND FUNCTIONS, WHEREIN DEMAND DEPENDS UPON THE SUM OF MONEY PRICE AND TIME COST, MAY BE OBTAINED FROM NEOCLASSICAL DEMAND THEORY WITHOUT RESORTING TO THE USE OF LEISURE, OR THE CONSUMER PRODUCTION FUNCTIONS OF THE BECKER MODEL. THE RESTRICTIONS ON THESE DEMAND FUNCTIONS PROVIDE AN INDIRECT MEANS OF ESTIMATING THE VALUE OF TIME. IN THE EMPIRICAL SECTION, THE VALUE OF TIME IS ESTIMATED FROM AIR TRAVEL DATA AND IS DERIVED, VIA THE INDIRECT PROCEDURE DEVELOPED, FROM OTHER DEMAND STUDIES. /DOT/